Sustaining local community economy through tourism: Melaka UNESCO world heritage city - Ab Rahman, Syakir Amir; Mohamed Osman, Mariana; Bachok, Syahriah; Ibrahim, Mansor (Elsevier, 2015)
Tourism has been one of the largest contributors towards Malaysian GDP over the last three decades. In essence, Malaysia generated 1,795,500 employments in 2013 of which some 6.5% of the total employment was created in the tourism sector. The study deals with extraction of tourists’ expenditure in five tourism sectors, accommodation, food and beverages, entertainment, shopping and transportation that lead to direct community benefits. Diary record survey was conducted at three different groups of selected hotels based on stars ratings- 5 & 4 stars hotel; 3,2 & 1 stars hotel; and budget hotels. The total number of 1500 survey booklets was distributed, only 1000 surveys were collected. The preliminary findings suggested that tourists spent 64.7% of their expenditure for transportation and only 1.4% for shopping. On average, it was also found that actual expenditure was rated at RM172 against the budgeted amount of RM306 per day. 34.3% of tourists spent were channeled to the local community. This study identifies and assesses Melaka’s position as an affordable tourist destination and how tourism indeed contributed to the local population indeed positively promotes the sustenance of and directly benefits their economic well-being.